Brill’s Encyclopedia of the Middle Ages - Melville, Gert, 1944-; Staub, Martial, 1964- (Brill's Medieval Reference Library Online,, 2016)
Brill's Encyclopedia of the Middle Ages Online offers an accessible yet engaging coverage of medieval European history and culture, ca. 500 - ca. 1500, in a series of themed articles, taking an interdisciplinary and comparative approach. Presenting a broad range of topics current in research, the encyclopedia is dedicated to all aspects of medieval life, organized in eight sections: Society; Faith and Knowledge; Literature; Fine Arts and Music; Economy; Technology; Living Environment and Conditions; and Historical Events and Regions. This thematic structure makes the encyclopedia a true reference work for Medieval Studies as a whole. It is accessible and concise enough for quick reference, while also providing a solid grounding in a new topic with a good level of detail, since many of its articles are longer than traditional encyclopedia entries. The encyclopedia is supported by an extensive bibliography, updated with the most recent works and adapted to suit the needs of an Anglophone audience.